Delayed intracerebral hemorrhage after ventriculoperitoneal shunting - (:unkn) unknown (My University, 2004)
Delayed intracerebral hemorrhage after ventriculoperitoneal shunt insertion is a rare complication. Here in we report the case of an 83-year-old female patient with a left posterior cerebral artery aneurysm and hydrocephalus. A hemorrhage at site of insertion was diagnosed on the postoperative day 4 after ventriculoperitoneal shunt insertion. The causative factor in our patient was probably the disruption of an intracerebral vessel by the ventricular catheter which was initially tamponaded by the intraparenchymal pressure, but later became manifest as the shunt became functional.
Keywords: Intracerebral hemorrhage; Shunt complication; Ventriculoperitoneal shunt